2006
DOI: 10.1111/j.1478-405x.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Extragastric Manifestations of Helicobacter pylori Infection – Other Helicobacter Species

Abstract: Recent studies have indicated a strong link between Helicobacter pylori and idiopathic thrombocytopenic purpura and iron deficiency anemia. Interesting results have also been obtained for ischemic heart disease, though most putative associations between H. pylori infection and extragastric disease remain speculative. With regard to other Helicobacter species, Helicobacter felis has been shown to play a role in gastric carcinogenesis in mouse models. An increased susceptibility to cholesterol gallstone formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Selenium, as in the form of selenocysteine, is involved in glutathione peroxidase, iodothyronine de-iodinase, and thioredoxin reductase enzymes [7]. Several studies have shown that H. pylori infection has relations to the deficiencies in copper, vitamin B12, folic acid, and vitamin A, C, and E [5,[8][9][10][11]. These deficiencies may be derived from anorexia caused by dyspeptic symptoms or from malabsorbtion secondary to intestinal bacterial infections, which is the result of hypo-achlorhydria in the stomach in the presence of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium, as in the form of selenocysteine, is involved in glutathione peroxidase, iodothyronine de-iodinase, and thioredoxin reductase enzymes [7]. Several studies have shown that H. pylori infection has relations to the deficiencies in copper, vitamin B12, folic acid, and vitamin A, C, and E [5,[8][9][10][11]. These deficiencies may be derived from anorexia caused by dyspeptic symptoms or from malabsorbtion secondary to intestinal bacterial infections, which is the result of hypo-achlorhydria in the stomach in the presence of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Hp -I is strongly associated with idiopathic thrombocytopenic purpura [29], and long-term platelet responses to Hp eradication have been reported in Canadian patients with idiopathic thrombocytopenic purpura [30]. Hp urease B antibody could cross-react with human platelet glycoprotein IIIa and partly inhibit platelet aggregation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Besides gastric disorders, the Hp etiology is discussed in connection with the development of different extra-gastric diseases such as vascular, skin and autoimmune diseases such as autoimmune thyroiditis (De Koster et al 2000;Solnic et al 2006). In several studies, increased prevalence of Hp infection in patients with AT was observed and confirmed not only by higher anti-Hp IgG levels but also positive urea breath tests (De Luis et al 1998).…”
Section: Abbreviations Hpmentioning
confidence: 99%